Fermentasi Fermentasi Asam Asetat Dari Nira Nipah Menggunakan Acetobacter Pasteurianus Dengan Variasi Waktu Dan pH Awal Fermentasi - Tantri Wilinda Julia; Chairul Chairul; Sri Rezeki Muria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Indonesia has 23% of world’s mangrove ecosystems, add up to 3.489.140,68 hectares with nipah plants (Nypa Fruticans) as one of the largest. Nipah sap is one of the products obtained from young fruit bunches with high sugar content that providing an opportunity as an alternative raw material for the production of acetic acid. Acetic acid can be produced from sugary materials through a fermentation process using microorganisms. This study was taken up to evaluate the role of some paramaters like initial pH and incubation period on acetic acid production from nipah sap by two simultaneous stages of fermentation using Saccharomyces cerevisiae and Acetobacter pasteurianus. Nipah sap after acid hydrolysis using 3 g/L oxalid acid were used as substrate for bio-ethanol production. Sugar contents of 417,71 g/L, temperature of 30°C, initial pH 4,5 and incubation period of 24 hours, inoculum of S.cerevisiae 10% (v/v) produced 10% (v/v) bio-ethanol. This medium were used as substrate to produced acetic acid using A.pasteurianus. Initial pH variation of 5, 5,5 and 6 and incubation period of 1,3 5, 7 and 9 days. The highest concentration of acetic acid obtained is 31,046 g/L and 30,56 %yield on the 5th day of acetic acid fermentation at the initial pH fermentation 5,5.Keywords: acetic acid, Acetobacter pasterian, fermentation, initial pH, nypa sap.